Expectativas de la familia indígena frente a la educación. Análisis de caso en la comunidad la candelaria, parroquia Cangahua - Tipanluisa Umaquinga, Luis Rodrigo (2018)
The present investigation has as purpose to know the different expectations that the indigenous family has in front of the education in the Candelaria community, Cangahua Parish, to demonstrate how education helps to improve the welfare of the family, community and the individual itself. In order to execute and develop the present case study, the qualitative method was used, through direct observation and recorded interviews, which were applied to the parents, the governing body of the community and former students of the educational institution. After collecting several information from different characters and verifying the different expectations that the indigenous family has regarding education, it was shown that education presents an improvement but does not cover the needs and worse the expectations, where community education follows the steps of the teaching and learning of the urban sector, assuming that it is a big problem for development, since the reality and the environment in which it is located are different. The community itself seeks to reclaim and strengthen its culture and identity through education through moments of coexistence and dialogue in cultural spaces. The members of the community and the family through education, try to have a better lifestyle both in the labor and economic aspect, in order to cover some expectations, they have for the future.